2019
DOI: 10.1016/j.hlc.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Female False Positive Exercise Stress ECG Testing – Fact Versus Fiction

Abstract: These data suggest that F+ stress ECG tests are frequent and equally common in women and men. However, most F+ stress ECGs in men can be predicted before the test, while most in women cannot. Being female may be a risk factor in itself. These data reinforce the value of stress imaging, particularly in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…This does reflect real world experiences and this particular study population. 18,42,43 The investigators were not blinded to the results of the stress test, making it possible for biases (including ascertainment bias) to occur. Overall event rates were low, especially in the non-ischemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…This does reflect real world experiences and this particular study population. 18,42,43 The investigators were not blinded to the results of the stress test, making it possible for biases (including ascertainment bias) to occur. Overall event rates were low, especially in the non-ischemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Bangladesh concluded that the ETT was more sensitive for males, while the females were prone to have false-positive results in this regard [12]. Furthermore, another study reports that females have a greater risk of false-positive ETT, which has led to the use of more invasive radiological modalities (magnetic resonance imaging or radioactive scans) for initial evaluation of CAD [14,15]. Pertinently, women have a higher predisposition toward falsepositive results, and they should be investigated and managed with caution, and further evaluation should be considered [15].…”
Section: Discussionmentioning
confidence: 99%
“…There were significantly less women than men (a common problem in cardiac research). This does reflect real‐world experiences and this particular study population 18,50,51 . The investigators were not blinded to the results of the stress test, making it possible for biases (including ascertainment bias) to occur.…”
Section: Discussionmentioning
confidence: 99%
“…To have completed this analysis with complete data rather than imputation of missing values may not have been associated in an epidemiological context with substantial bias in reported regression estimates. 15,49 The multivariable prediction model described in the present study was derived from echocardiographic observations at a single center. There were significantly less women than men (a common problem in cardiac research).…”
Section: F I G U R Ementioning
confidence: 99%